2017
DOI: 10.1177/0013161x17735869
|View full text |Cite
|
Sign up to set email alerts
|

Will Decentralization Affect Educational Inequity? The Every Student Succeeds Act

Abstract: In December 2015, President Obama signed the Every Student Succeeds Act, which was a long overdue reauthorization of the Elementary and Secondary Education Act. What is remarkable about this new federal legislation is that it explicitly reverses the decades-long federal effort to more tightly couple the U.S. educational system. While not removing testing requirements, the legislation dramatically reduces the federal role in shaping education policy, returning significant power to the states to design education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 49 publications
(46 reference statements)
1
28
0
Order By: Relevance
“…This body of literature also shows that while an understanding of equity centered on equal access and opportunity remains prevalent (Bulkley, 2013;Verstegen, 2015), outcome equity has been given more attention in recent education policy in the era of standards-based, consequential accountability (Bulkley, 2013;Cochran-Smith et al, 2018;Thomas & Brady, 2005). From a policy history perspective, ESSA maintains NCLB's equity commitment by improving the educational experiences and results of historically disadvantaged student populations yet shifts the policy making power back to the state education agencies to develop policies and accountability measures in enhancing equity in their schools (Cook-Harvey et al, 2016;Egalite et al, 2017;Knight, 2019). Therefore, it is important to establish a clearer view of state education policy makers' understandings of equity and provisions in support of such equity visions in their ESSA plans.…”
Section: Conceptualizing Equity In Education Policymentioning
confidence: 99%
See 2 more Smart Citations
“…This body of literature also shows that while an understanding of equity centered on equal access and opportunity remains prevalent (Bulkley, 2013;Verstegen, 2015), outcome equity has been given more attention in recent education policy in the era of standards-based, consequential accountability (Bulkley, 2013;Cochran-Smith et al, 2018;Thomas & Brady, 2005). From a policy history perspective, ESSA maintains NCLB's equity commitment by improving the educational experiences and results of historically disadvantaged student populations yet shifts the policy making power back to the state education agencies to develop policies and accountability measures in enhancing equity in their schools (Cook-Harvey et al, 2016;Egalite et al, 2017;Knight, 2019). Therefore, it is important to establish a clearer view of state education policy makers' understandings of equity and provisions in support of such equity visions in their ESSA plans.…”
Section: Conceptualizing Equity In Education Policymentioning
confidence: 99%
“…All 52 state plans incorporated information about these mandatory student groups, yet the majority of them focused only on low-income students and minority students and used verbatim words from the U.S. DoE template with few or no substantial, state-specific modification for the other groups. This practice suggested that, instead of maximizing the policy flexibility afforded by ESSA (Egalite et al, 2017), SEAs still chose to follow the federal prescription and did not go beyond what was minimally required.…”
Section: Focal Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools and districts from every state were now accountable to federal student performance mandates that aligned assessments to state content standards. Annual assessments in ELA were required for all students in grades 3-8 and once during high school (Egalite, Fusarelli, & Fusarelli, 2017;McGuinn, 2016). In an attempt to guarantee educational equity, states were required to report the level of student proficiency as measured by adequate yearly progress (AYP) for all relevant student subgroups, including gender, race/ethnicity, poverty, disability, and English language status (Haertel & Herman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The reauthorization also maintained a focus on the idea of educational equity through assessment, requiring the reporting of student subgroup performance on two new student subgroups: gender and migrant status (National Conference of State Legislatures, 2015). While there were some noticeable differences between ESSA and NCLB, using assessments to attempt to improve student achievement in underperforming schools remained a fundamental focus of federal education policy (Egalite et al, 2017;McGuinn, 2016).…”
Section: Introductionmentioning
confidence: 99%